2013
DOI: 10.3846/13923730.2012.734852
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Perception of Safety Among Taiwan Construction Managers

Abstract: Using Statistical Package for the Social Science (SPSS) and Structural Equation Modeling (SEM), this study develops a model to evaluate construction managers' perception of safety as relates to six aspects: human error (HE), safety resource and application (SRA), safety equipment and training (SET), site culture and external factors (SCF), safety inspection and audit (SIA), and accident medium and activities (AMA). The model was used to identify and compare the level of safety perceived by Taiwanese constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…This study builds on the current body of literature on source protection in Taiwan and internationally, by investigating the underlying relationships between CSFs for DWSP programs based on the opinions of industry practitioners. The approach of using SEM for investigating underlying structures is frequently used for understanding latent structures and relationships that cannot be easily measured directly [10].…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This study builds on the current body of literature on source protection in Taiwan and internationally, by investigating the underlying relationships between CSFs for DWSP programs based on the opinions of industry practitioners. The approach of using SEM for investigating underlying structures is frequently used for understanding latent structures and relationships that cannot be easily measured directly [10].…”
Section: The Present Studymentioning
confidence: 99%
“…The SEM method supports the examination of the hypothetical relationships between variables and verifies the relationship statistically [8]. This approach has been used in a variety of safety-related research, including safety culture and construction safety, where there is a complex mix of policy, operations and multiple agencies [9,10]. A deeper understanding of CSFs which influence DWSP program success using SEM can help guide better practice for multi-agency management of water catchments for control of water quality and public health risks in drinking water supplies.…”
Section: Introductionmentioning
confidence: 99%
“…us, a certain proportion of engineering costs should be allocated to safety management. Personal attitude [10,11,51,56,58] Personal attitude entails the intrinsic motivation of workers to actively participate in safety management practices.…”
Section: Numbermentioning
confidence: 99%
“…Safety on site should be discussed at management meetings and safety recognition and incentive programs should be developed (Belel and Muhmud[5]). However, Chenet al, [8] have identified public works managers and design and audit managers have lower level of perceived safety than contractor managers do (Chen et al, [8])( Table 3). Reinforcing the perception of safety between these two types of construction personnel is important to reduce construction accidents (Chen et al, [8]).…”
Section: Mahalingam and Raymondmentioning
confidence: 99%